Developing multitrack towards excellence UMP academicians' career path - Nor Alisa, Mohd Damanhuri; Siti Zanariah, Satari; N., Masngut; Roslinazairimah, Zakaria; Rozieana, Khairuddin (2018)
A career as an academician entails far beyond teaching. Many are attracted to academia because they want to be able to conduct research in their interest. Some of the other reasons to be an academia are the desire to teach and help others to develop, have more freedom, independence and flexibility, greater job security, a clear career progression track, and a decent salary. The key of this paper is to design an academic differentiated career pathways (ADCAP) for Universiti Malaysia Pahang (UMP) academicians’ to manage the career progression, identify one career inclination and as a checklist of one achievement. UMP academician is most likely to encounter their role model in teaching, research and professional service environments which are the platforms in pursuit towards excellence. Thus, ADCAP comprises three career tracks: educator, researcher and industrial practitioner. It is critically important that the junior academicians’ be familiar with the requirements of their particular track in the early career so that they are well equip with the relevant requirements and expectations for promotion and be preparing about these matters from an early point in his career, rather than near the end when the promotion clock is ticking.